Converting RPL into academic capital: Lessons from Australian universities - Pitman, Tim; Vidovich, L. (Routledge, 2013)
Recognition of prior learning (RPL) requires an assessment of the equivalence and transferabilityof learning acquired in one context to another. However, this study’s examinationof the institutional policies and practices of three Australian universities reveals thatRPL can also be understood as a Bourdieuian process of ‘capital conversion’, where anindividual’s economic, social and cultural capital are assessed as being equivalent to ‘academicexperience’. This approach reveals that, far from being an epistemological assessmentof prior learning, universities also consider their organisational identity and statuswhen considering what informal or non-formal learning will be accepted. Ultimately, whatcounts as prior learning depends as much upon which university is doing the assessment,its motive for doing so and the extent to which it views RPL as a normative threat.